An increase in livestock density increases forage nutritional value but decreases net primary production and annual forage nutritional yield in the alpine grassland of the Qinghai-Tibetan Plateau - Yao, Xixi; Li, Changhui; Ahmad, Anum Ali; Tariq, Akash; Degen, A. Allan; Bai, Yanfu (Frontiers in Plant Science, 2022)
Pasture biomass and quality are dependent on herbivore grazing and precipitation, but the responses of vegetation to the interactive effects of climate and grazing regimes remain unclear. We conducted an eight-year sheep grazing experiment with 4 stocking rates (0, 3.5, 5.5, and 7.5 sheep/ha) in an alpine meadow of the northeastern Tibetan Plateau. The above-ground net primary productivity (ANPP) and forage nutritional value (FNV) of four dominant species (Poa annua, Kobresia humilis, Astragalus adsurgens and Potentilla fruticosa) were measured during a wet year (360 mm rainfall) and a drought year (216 mm rainfall). The FNV was used as indicator of forage quality and was calculated from the crude protein (CP) content, in vitro true dry matter digestibility (IVTD), metabolic energy (ME) yield, and neutral detergent fiber (NDF) content of the plant. The stocking rate explained a minimum of 76% of the variations of ANPP, and the precipitation sub-additive effect for ANPP ranged from 5% to 12%. The interaction of sheep stocking rate and precipitation affected ANPP of the 4 species, except for P. fruticosa. The FNV of the pasture increased with increasing grazing pressure, but ANPP and forage nutritional yield (FNY) decreased. In calculating FNY, the increase in FNV did not compensate for the decrease in ANPP. In non-grazed plots, the CP yield declined sharply (18%-55%) in response to drought, but there was no effect on ME yield. The interaction between stocking rate and precipitation affected forage quality of the 4 plant species differently. The grassland ANPP and FNY could be maintained at a grazing intensity of 3.5 sheep/ha in wet and dry years. Our results highlight that stocking density affects pasture ANPP and FNV, and is contingent on rainfall.